A framework for evaluating migration strategies of evolving business processes. (15th August 2021) - Khebizi, Ali; Seridi-Bouchelaghem, Hassina
In the dynamic business process evolution context, the problem of managing active instances migration has been addressed from different perspectives and the research literature exhibits a panoply of instances migration strategies. But, it's observed that there is no widely-accepted benchmark to evaluate the proposed strategies. As a result, it can be difficult for a protocol manager to select the suitable migration strategy for a given evolution scenario. To address this challenge, we propose a comprehensive framework and we provide computational models for evaluating and comparing migration strategies intended to handle impact of business processes changes. In our approach, selecting the best migration strategy is perceived as an optimisation problem for which a migration cost model is suggested and an associated objective function is formalised. The proposed framework can be used by business processes managers to efficiently choose the most adequate migration strategy for a given evolution context.